Assessment of After-School Programs according to the Views of School Principals and Parents - Esin ACAR; Ruken AKAR VURAL (Elementary Education Online, 2023)
In the study, after-school education programs (ASEP) conducted in private and public primary schools and the places located out of school are evaluated according to parents and school administrators’ views. The data were collected through face-to-face individual interviews and focus group interviews. The thoughts embodied by the classification process made by what the participants say are revealed in a descriptive way. The socio-economic status, parental involvement, functions of educational programs, coordination of after-school programs and school programs, process of the programs are discussed in the way of both positive and negative. Both parents and school administrators reported mostly positive comments on the content, implementation and purpose of after-school practices. However, it has been stated that there are problems on some issues such as the functioning of the programs and the physical conditions affecting this function, insufficient time, the school's teaching system, and the sufficiency of the trainers.